Issue of Consumers Burden: The Role of Taxation and Economic Growth in Malaysia - Norsiah, Ahmad; Siti Nurhazwani, Kamarudin; Loganathan, Nanthakumar (2017)
With the recent debatable issue on the newly implemented tax reforms and the progressive economic development in Malaysia, this study intends to explore the effects of taxation and economic growth on consumers burden in Malaysia. The inquiry of such relationship is crucial in view of the current increase of living cost that is experienced by Malaysian consumers. The analysis was conducted using the Autoregressive Distributed Lag (ARDL) estimation and Granger causality testing on the quarterly time series data for the period of 1996-2016. Consequently, the results from this study provided evidence on the existence of long run relationship between the consumers‟ burden-taxation-growth nexus. Additionally, other major findings by the ARDL short and long run analysis revealed that indirect taxes significantly affected consumers‟ burden in the short run only while economic growth of the nation have both short run and long run impact on consumers burden.